miR-196a-5p-Rich Extracellular Vesicles from Trophoblasts Induce M1 Polarization of Macrophages in Recurrent Miscarriage - Jing Zhang; Yu Tao; Renfei Cai; Yao Wang (Journal of Immunology Research)
Purpose. Numerous studies have described the presence of crosstalk between trophoblasts and macrophages and the critical role it plays in recurrent miscarriage (RM). However, the mechanism of trophoblast-derived extracellular vesicle (EV) miRNAs and their interactions with decidual macrophages in the pathogenesis of RM remains unclear. Materials and Methods. miRNA-seq was used to identify the differentially expressed miRNAs between RM patients and healthy controls. qPCR and in situ hybridization assays were performed to analyze the expression levels of miR-196a-5p in RM. THP-1 cells were treated with EVs, and qPCR and flow cytometry were performed to explore the polarization of macrophages. To explore the crosstalk between trophoblasts and macrophages, a coculture model and a series of cell function assays were performed. Results. We first demonstrated that miR-196a-5p expression was higher in the cytotrophoblasts of villous tissues and plasma EVs from RM patients. miR-196a-5p derived from trophoblasts could be transferred into macrophages via EVs to induce M1 polarization via IκBα-mediated NF-κB pathway. Moreover, we found that M1 macrophages induced by EV miR-196a-5p derived from trophoblasts conversely regulated the proliferation, migration, and apoptosis of trophoblasts via TNF-α. Conclusions. This study indicated that trophoblast-derived EV miR-196a-5p was positively associated with RM and functioned by regulating the crosstalk between trophoblasts and macrophages. These findings may attribute to identify a novel biomarker specific for RM.